The development of the neurosurgery workforce in Austria over the past quarter century: is more always better? - Mischkulnig, Mario; Polacsek-Ernst, Roland; Körner, Lisa I.; Frischer, Josa; Diendorfer, Cornelia M.; Matula, Christian; Roessler, Karl; Widhalm, Georg; Dorfer, Christian (Frontiers in Medicine, 2025)
BackgroundThe neurosurgical workforce has expanded markedly across Europe, often accompanied by declining operative exposure per surgeon. Austria, with one of the highest physician and hospital bed densities in the OECD, provides an important case study to assess whether workforce expansion has translated into proportional service provision and maintained training opportunities.MethodsWe performed a retrospective, nationwide analysis of official health statistics from Statistik Austria covering 1997–2023. Data included numbers of practicing neurosurgeons, all specialist physicians, population counts, neurosurgical beds, inpatient stays, and cranial procedures. Absolute and per-capita developments were assessed, and services were related to neurosurgeon density. Statistical analyses comprised Kendall’s tau-b, Wilcoxon signed-rank, and Friedman tests.ResultsThe number of practicing neurosurgeons in Austria increased from 97 in 1997 to 301 in 2023 (+ 210.3%), rising from 1.22 to 3.30 per 100,000 inhabitants (+ 170.5%). Growth in neurosurgeon density significantly outpaced both population growth (+ 14.3%) and the overall increase of specialist physicians (+ 77.4%, p = 0.001). Despite this expansion, absolute service provision showed only negligible to moderate increases (beds + 4.7%, inpatient stays + 28.6%, cranial procedures + 0.1%). Adjusted for workforce size, services per neurosurgeon declined sharply: cranial procedures decreased by –67.8%, inpatient stays by –58.6%, and neurosurgical bed capacity per surgeon by –66.3% (all p < 0.001). Regional disparities were pronounced, with Salzburg reaching 6.51 neurosurgeons per 100,000 while Burgenland registered its first only in 2012 and still shows the nationwide lowest density of 1.00 per 100,000.ConclusionAustria has experienced rapid workforce growth without a parallel rise in neurosurgical case volume, resulting in declining operative exposure per surgeon. These findings highlight risks for training quality, efficiency, and future competitiveness. Evidence-based workforce planning, structured regulation of training intake, and expansion of outpatient neurosurgical services will be essential to ensure sustainable care and safeguard international standards of neurosurgical education.